Eksplorasi Bahasa Jawa Pra-Sekolah di Desa Jumapolo, Karanganyar - Amalia Wulan Sari; Oktiva Herry Chandra (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The exploration of Javanese language in children encompasses language attitudes and the process of grammar system formation in children. The growth and development of children with the Javanese language are influenced by their mother tongue and environment. Factors influencing language acquisition in children include the social environment, which in this study includes teachers and students at Jumapolo 01 Kindergarten. This research examines the intensity of Javanese language interaction in the domestic domain and the influence of Indonesian. The study aims to understand the language attitudes of children from Jumapolo 01 Kindergarten and their syntactic level. Data collection was conducted through active participatory observation, using observation, involvement, and conversation techniques. The data were then reduced and analyzed based on syntactic theory. Finally, conclusions were drawn from the research findings regarding language attitudes and syntactic phenomena observed in sentence patterns produced by Jumapolo 01 Kindergarten students. This study reveals that preschool students at Jumapolo 01 Kindergarten predominantly choose to use Javanese in conversations with friends and educators. The sentence patterns produced by Jumapolo 01 Kindergarten students demonstrate an ability to form clear and efficient sentences. Although there are some sentence pattern errors, the sentences are still acceptable between speakers and listeners.